Integration of PM1200 and IoT for Electrical Energy Monitoring with Web-Based Map Visualization - Nor, Syafriyadi; Ahyadi, Zaiyan (P3M Politeknik Negeri Banjarmasin, 2025)
This study aims to integrate the PM1200 device with Internet of Things (IoT) technology using the Modbus protocol to enable real-time monitoring of electrical energy. The current challenge lies in the limited flexibility of energy monitoring, which is typically restricted to local access and lacks map-based visualizations. To address this, the system integrates interactive maps to provide a clearer and more comprehensive view of energy distribution across different locations. This study seeks to offer an effective energy monitoring solution with data visualized through maps on an interactive web platform. The methodology includes reading data from the PM1200 device via the Modbus protocol, transmitting it to an IoT platform using the MQTT protocol, and displaying the data as maps on a web interface. The findings are expected to support effective energy monitoring and enhance energy management efficiency.